TINGKAT KEAMANAN MINUMAN INFUSED WATER DENGAN DIVERSIFIKASI PENYIMPANAN YANG BERBEDA - Surati Surati; Nurul Qomariah (Jurnal Riset Kesehatan, 2017)
Background: Water is one of the components required in human life. Three requirements of clean water in physics, chemical and bacteriological must have a raw quality requirements according to Standar Nasional Indonesia (SNI). Infused Water beverages is water that has been given an extra piece of fruits that give the sensation of flavour and have much benefits for health. Infused Water became known and consumed by most people of Indonesia because the manufacturing process is very easy, using local fruits and have much benefits because it contains vitamins and minerals. The purpose of research is to determine the level of security of Infused Water beverages with different storage diversification and then matched with Standar Nasional Indonesia (SNI) 7388:2009. As for the benefits of this research is to be able to add a list of healthy and nutrition beverages.  Types of research: Experiment with a completely randomized design (RAL), data analysis to determine the effect of different storage towards security of Infused Water beverages then tested with normality of data using Shapiro Wilk. After the data have normal distribution then using Anova test. Research result: Sample code (AP, BP, CP, AD, BD, CD) of Angka Lempeng Total (ALT) examination qualified in Standar Nasional Indonesia (SNI) No. 01-3553-2006. There after do the estimators test, a confirmation test and Angka Paling Mungkin (APM) test that has been qualified in SNI 7388:2009. Conclusion: Examination result of Angka Lempeng Total (ALT) and Most Probable Number Coliform all samples comply the requirements of SNI, accordinglyInfused Water has been decent for consumption.